2018
DOI: 10.1115/1.4039271
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Near-Nozzle Spray Performance of Gas-to-Liquid and Jet A-1 Fuels Using Shadowgraph and Phase Doppler Anemometry

Abstract: The gas-to-liquid (GTL) fuel, a liquid fuel synthesized from natural gas through Fischer–Tropsch process, exhibits better combustion and, in turn, lower emission characteristics than the conventional jet fuels. However, the GTL fuel has different fuel properties than those of regular jet fuels, which could potentially affect its atomization and combustion aspects. The objective of the present work is to investigate the near-nozzle atomization characteristics of GTL fuel and compare them with those of the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Therefore, as the ligament diameter increases, the droplet diameter also increases. In concordance with Shinjo et al 58 's study, the results also show an increase in droplet diameter with an increase in ligament diameter. This increase in the diameter of the droplet is mainly due to the effect of viscosity.…”
Section: Formation Of Ligaments and Dropletssupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, as the ligament diameter increases, the droplet diameter also increases. In concordance with Shinjo et al 58 's study, the results also show an increase in droplet diameter with an increase in ligament diameter. This increase in the diameter of the droplet is mainly due to the effect of viscosity.…”
Section: Formation Of Ligaments and Dropletssupporting
confidence: 92%
“…A similar approach has been used by Kannaiyan et al 29 for finding the sheet breakup length for nanoparticles-loaded aviation turbine fuel and (GTL) gas-to-liquid fuel. 58 Experimental results show that the break-up length was high for JB20 and JB30 at low M (see Figure 10(b)). With an increase in M , the break-up length was reduced due to higher atomizing air velocity ( u g ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Earlier, the effects of fuel properties [10][11][12][13] and nanoparticle dispersion [14,15] on the NG-SPK jet fuel atomization were reported at atmospheric ambient conditions. Results from those studies indicated a minimal influence of fuel characteristics on atomization, resulting in comparable performance between conventional and alternative jet fuels at such conditions.…”
Section: Introductionmentioning
confidence: 99%